Practices related to tobacco sale, promotion and protection from tobacco smoke exposure in restaurants and bars in Kampala before implementation of the Uganda tobacco control Act 2015 - Kabwama, Steven Ndugwa (Tob Induc Dis, 2017)
BACKGROUND: The Word Health Organization’s Framework Convention on Tobacco Control calls on parties to implement evidenced-based tobacco control policies, which includes Article 8 (protect the public from exposure to tobacco smoke), and Article 13 (tobacco advertising, promotion and sponsorship (TAPS)). In 2015, Uganda passed the Tobacco Control Act 2015 which includes a comprehensive ban on smoking in all public places and on all forms of TAPS. Prior to implementation, we sought to assess practices related to protection of the public from tobacco smoke exposure, limiting access to tobacco products and TAPS in restaurants and bars in Kampala City to inform implementation of the new law. METHODS: This was a cross-sectional study that used an observational checklist to guide observations. Assessments were: whether an establishment allows for tobacco products to be smoked on premises, offer of tobacco products for sale, observation of tobacco products for sale, tobacco advertising posters, illuminated tobacco advertisements, tobacco promotional items, presence of designated smoking zones, no-smoking signs and posters, and observation of indoor smoking. Managers of establishments were also asked whether they conducted tobacco product sales promotions within establishments. Data were collected in May 2016, immediately prior to implementation of the smoke-free and TAPS laws. RESULTS: Of the 218 establishments in the study, 17% (n = 37) had no-smoking signs, 50% (n = 108) allowed for tobacco products to be smoked on premises of which, 63% (n = 68) had designated smoking zones. Among the respondents in the study, 33.3% (n = 72) reported having tobacco products available for sale of which 73.6% (n = 53) had manufactured cigarettes as the available tobacco products. Eleven percent (n = 24) of respondents said they conducted tobacco promotion within their establishment while 7.9% (n = 17) had promotional items given to them by tobacco companies. CONCLUSION: Hospitality establishments in Kampala are not protecting the public from tobacco smoke exposure nor adequately limiting access to tobacco products. Effective dissemination of the Tobacco Control Act 2015 is important in ensuring that owners of public places are aware of their responsibility of complying with critical tobacco control laws. This would also likely increase self-enforcement among owners of hospitality establishments and public patrons of the no-smoking restrictions.